The coach development framework for the International Ice Hockey Federation - Kubischta, F. (Haaga-Helia University of Applied Sciences, 2018)
The here presented Master`s Thesis had as its objective to create a Coach Development Framework (CDF) for the International Ice Hockey Federation (IIHF).